Endogenous transport costs and international trade - Kurt A. Hafner; Jörn Kleinert; Julia Spies (The World Economy, 2022)
In this paper, we model a manufacturing and a transport sector and use export volumes to determine the demand for transport services. If trade exceeds a particular level, transport service suppliers maximise profit by investing in an advanced transport technology, which lowers their marginal costs and reduces equilibrium transport prices. Transport costs thus vary according to two characteristics: the distance between two locations and the endogenous firm decision to invest in transportation. A simulation exercise reveals that ignoring the effect of the investment decision on transport costs biases empirical results. We apply this insight in our empirical estimations which rely on repeatedly collected transport price data from the United Parcel Service. We use an instrumental variable estimator to account for the endogeneity of the investment decision. Our estimation results confirm that transport prices are influenced by both the distance and the level of exports between two countries. We find that trading partners with 10% more exports enjoy on average 0.6% lower transport prices.
Keywords: 330; distance; endogenous transport costs; OLS/Poisson estimation